CsPbBr3 perovskite nanocrystals as highly selective and sensitive spectrochemical probes for gaseous HCl detection. Issue 2 (12th December 2016) - Chen, Xiao; Hu, Huawei; Xia, Zhaoming; Gao, Wei; Gou, Wangyan; Qu, Yongquan; Ma, Yuanyuan
Abstract : A rapid and facile gaseous anion-exchange reaction between CsPbBr3 perovskite nanocrystals and HCl vapor was carried out under the ambient conditions. Abstract : A rapid and facile gaseous anion-exchange reaction between CsPbBr3 perovskite nanocrystals and HCl vapor was carried out under the ambient conditions. The resultant CsPb(Br/Cl)3 nanocrystals preserved the morphological features and crystal structure of the original CsPbBr3 nanocrystals and exhibited a significant blue-shift in the ultraviolet-visible light absorption and photoluminescence spectra. Inspired by the visual observations in the fluorimetry upon gaseous anion-exchange reaction, the CsPbBr3 nanocrystals were developed as highly sensitive and selective spectrochemical probes for the detection of toxic and corrosive HCl vapor with a concentration as low as 5 ppm.